Replaced by Machines? The Intelligent (Ro)Bots as the Disruptive Innovation for Human Workforce in Cross Cultural Perspective - Modliński, Artur; Bartosiak, Marcin (Facets of Managing in Cross-Cultural Diversity, 2021)
The rise of artificial intelligence (AI) and its growing capacity in sensing, cognizing, and performing, is directly exposing the human workforce to the competition with more and more intelligent machines. The potential replacement of the human workforce by AI has become the starting point for a scientific discussion not only for human resources management, but also for organizational anthropology and cross-cultural management. Managers should know the nature of machines replacing humans, and develop strategies to deal with the phenomenon. This chapter presents examples of professions that can be replaced by technology. It also shows a case where such a replacement has already happened. It tries to answer the question if the human workforce can be universally (globally) “disrupted” by autonomous technologies, and it lies the foundation for future research regarding the acceptance of technology in various cultures.